The role of attainability and external focus of attention on standing long jump performance - King, Adam (2021)
BACKGROUND: External focus of attention (FOA) promotes enhanced performance and learning in comparison to internal FOA; however, several dimensions associated with external FOA appear to have varying influence on motor skill performance. AIM: The purpose of this study was to investigate whether an attainability aspect of external FOA elicits enhanced standing long jump performance. METHOD: Fifteen healthy males performed standing long jumps in the following conditions: without a visual target (Tno), target placed at maximum distance (Tmax), and a target placed 10% beyond maximum distance (Tmax+10). Jump distances were measured, and kinetic data were recorded using a force platform. RESULTS: One-way ANOVA showed significantly greater jump distances for Tmax+10 compared to Tno and Tmax (p < 0.01). Additionally, the impulse of the ground reaction force (GRFimpulse) in the anterior-posterior direction was significantly greater for Tmax and Tmax+10 compared to Tno (p < 0.05). CONCLUSION: Thus, an external FOA tailored to individual ability benefits standing long jump performance. Overall, the findings support the approach of adopting an external FOA with an emphasis on targets that are specific to the individual and based on attainability.